Ethics and Morality in Finance - Gupta, Rakesh; Sukumaran, Aswini (Prabandhan: Indian Journal of Management, 2013)
Recent financial crises have attracted significant debate in the media about the ethical and moral issues that ought to have been considered by the stakeholders involved in the market. This discussion has gained further traction in the aftermath of the global financial crisis of 2007-08. One of the factors that are being considered is based on the argument that the market is as good as its participants. If the market participants behave in a moral and ethical manner, the market outcomes are expected to be in the best interest of the society. This study reviews literature in the area of ethics and morality in business in general, and in finance, in particular. The researchers also looked at the emphasis academicians and market participants gave to ethics and morality in finance. Based on the research, the authors concluded that the issue of ethics and morality has been tested in the area of marketing and to a certain extent in accounting; whereas ethics and morality research has been largely ignored in finance and economics research. Origins of the words ethics and morality from religion and theology may have been a cause for academia in the field of finance and economics to shy away from identifying ethical and moral considerations in the practice of finance and economics.